Rindopepimut: a promising immunotherapeutic for the treatment of glioblastoma multiforme. (June 2014) - Swartz, Adam M; Li, Qi-Jing; Sampson, John H
Glioblastoma multiforme (GBM) is the most common and aggressive glial cell-derived primary tumor. Current standard of care for patients with GBM includes maximal tumor resection plus adjuvant radiotherapy and temozolomide chemotherapy, increasing median overall survival to a mere 15 months from diagnosis. Because these therapies are inherently nonspecific, there is an increased likelihood of off-target and incomplete effects; therefore, targeted modalities are required for enhanced safety and efficacy. Rindopepimut is emerging as a safe and potentially effective drug for the treatment of GBM. Rindopepimut consists of a 14-mer peptide that spans the length of EGF receptor variant III, a mutant variant of EGF receptor found on approximately 30% of primary GBM, conjugated to the carrier protein keyhole limpet hemocyanin. Vaccination with rindopepimut has been shown to specifically eliminate cells expressing EGF receptor variant III. Phase II clinical trials have suggested that vaccination of newly diagnosed GBM patients with rindopepimut plus adjuvant granulocyte–macrophage colony-stimulating factor results in prolonged progression-free and overall survival with minimal toxicity. This review will outline the development of rindopepimut, as well as the current status of this vaccine.